Association of Smoking Related to Knowledge, Attitude, and Practice (KAP) with Tobacco Use in Community Health Center Working Area of Sungai Durian, Sintang Regency, West Kalimantan Province - Maretalinia Maretalinia; Elvi Juliansyah; Suyitno Suyitno; Aris Yulianto; Dyah Suryani (Buletin Penelitian Sistem Kesehatan, 2021)
Tobacco use is one of the predicting factors of non-communicable diseases. In 2003, cigarette consumption was the main factor contributing to 4.9 million deaths in developing countries. In 2020, Bureau of Statistics Indonesia reported 31.5% of Indonesian population were tobacco users. Particularly, in West Kalimantan province, more than one-fourth of men are smokers. Specifically, in the working area of Sungai Durian Primary Healthcare Center, third-fourth of men are smokers. This study was conducted to examine the relationship between Knowledge, Attitude, and Practice (KAP) with tobacco use. This cross-sectional study employed 218 respondents of 4,321 male population. The predicting factors in this study were knowledge, attitude, and practice. The statistical test was done using univariate, bivariate (Chi-Square), and multivariate (binary logistic regression) analyses. The bivariate analysis test showed that knowledge and practice were significantly associated with tobacco use. Regarding the multivariate analysis results, practice was the strongest factor affecting tobacco use (AOR= 4.25, CI 95% (1.93 – 9.36)), and the second strongest factor was knowledge (AOR= 2.46, CI 95% (1.00 – 6.04)). Tobacco use in the working area of Sungai Durian Primary Healthcare Center was mostly affected by practice. Primary healthcare centers as the nearest healthcare facility in the community need to improve health education and decrease tobacco consumption. A tobacco control can be implemented by banning smoking indoors to reduce smoking behavior. Abstrak Penggunaan tembakau merupakan salah satu faktor risiko penyakit tidak menular. Pada tahun 2003, konsumsi rokok merupakan penyebab utama kematian 4,9 juta penduduk di negara berkembang. 31,5% penduduk Indonesia adalah pengguna tembakau berdasarkan data tahun 2000. Secara khusus di Provinsi Kalimantan Barat, lebih dari satu per empat laki-lakinya adalah perokok, dan secara lebih khusus lagi, tiga per empat laki-laki usia 20-30 tahun di wilayah kerja Puskesmas Sungai Durian adalah perokok. Studi ini dilakukan untuk menguji hubungan pengetahuan, sikap, dan perilaku terhadap penggunaan tembakau. studi cross-sectional ini melibatkan 180 perokok di antara 4,321 total populasi laki-laki. Faktor prediksi pada studi ini yaitu: pengetahuan, sikap, dan praktik. Uji statistik telah dilakukan yaitu uji tunggal, ganda (Chi-Square), dan multivariabel (binary logistic regression). Uji ganda menemukan bahwa pengetahuan dan perilaku secara signifikan berhubungan dengan penggunaan tembakau. Lebih jauh, berdasarkan hasil multivariabel, perilaku merupakan pengaruh terbesar (AOR= 4,25, CI 95% (1,93 – 9,36)) dan diikuti dengan pengetahuan (AOR= 2,46, CI 95% (1,00 – 6,04)). Penggunaan tembakau di wilayah kerja Puskesmas Sungai Durian sebagian besar dipengaruhi oleh perilaku. Puskesmas sebagai pelayanan kesehatan terdekat butuh menyelenggarakan pendidikan kesehatan untuk menurunkan konsumsi tembakau. Pengendalian tembakau yang diimplementasikan dengan larangan merokok di dalam ruangan sangat penting untuk mengurangi kebiasaan merokok.